Subungual Glomus Tumor- Clinical Presentation And Treatment - Debnath, Shyamal Chandra; Roy, Suman Kumar; Kairy, RR (Bangladesh Journal of Plastic Surgery, 2014)
Glomus tumor is a rare condition and constitutes only 1 % of all soft tissue tumor of body. Glomus tumor is familiar for its unusual presentation and long standing symptoms due to delay in diagnosis. Authors have presented the clinical behavior and treatment of 7 patients with subungual soft tissue mass. Following surgical excision, all patients cured of symptoms, at the end of follow up, no recurrence occurred; post operative nail deformity was insignificant. DOI: http://dx.doi.org/10.3329/bdjps.v3i2.18250 Bangladesh Journal of Plastic Surgery July 2012, 3(2): 45-48